A case study: promotional mix used in increasing sales of Dewan Pelajar magazine / Munirah Mohd Hazizan - Mohd Hazizan, Munirah (Faculty of Business and Management, 2010)
The ‘Dawama Sdn Bhd’ is the company that published many type books and magazines from ‘Dewan Bahasa dan Pustaka’. Due to limited of time, the issues only focus on ‘Dewan Pelajar’ magazine because the sales has decline from year to years. The purposes of the study is to find out the current promotion mix tool that used by the company and to determine the most effective tools of the promotional mix can be used by ‘DAWAMA’ to increase sales of the ‘Dewan Pelajar’ Magazine in the market. The company are effectively used its promotional mix in promoting the ‘Dewan Pelajar’ but still in moderate level. The company needs some improvement from company in order to make the promotional mix more affective from time to time even seem effective. The company should eliminating or improving the most ineffective promotional beside that their well plan to allocate the right budget so the promotion mix activity will be more effective